Characterization of CdS nanoparticles Prepared by Liquid – Liquid Interface Reaction - Shaban, Salma M.; Mahdi , Khalad T.; Ahmed , Ahmed S. (Iraqi Journal of Science, 2022)
Liquid – liquid interface reaction is one of the method to prepare nanoparticles, the preparation of nanoparticles depends on the super saturation of ions which can satisfy by layered two immiscible liquid (toluene and deionized (DI) water). The XRD-diffraction analysis give a mix structure from hexagonal and cubic and the average grain size is 7.73 nm using Sherrer relation and 9.54 nm using Williamson –Hall method. Transmission electron microscopy (TEM) Showed that the size of particles around 3 nm which is comparable with Bohr radius of CdS.From UV-Visible spectrum analysis which use two model to estimate the radius of particles , the first one is effective mass approximate (EMA) model and the second one is tight binding model , from the first model the estimated that the radius is 2.069 nm and from the second model. The estimated radius is 1.95 nm which is very comparable with Bohr radius of CdS and this give a strong quantum conferment that distinguish the proper of nano than a bulk.